Chitosan-Based Scaffolds Incorporated with Silver Nanoparticles for the Treatment of Infected Wounds - Sibusiso Alven; Blessing Atim Aderibigbe (MDPI AG, 2024)
Bacterial infections are major problems in wound care due to their impact on the retarded process of wound healing, leading to chronic wounds. Most of the presently utilized wound dressing products exhibit poor antimicrobial properties. Wound dressings formulated from chitosan have been reported to be effective for treating infected wounds, resulting from the antibacterial properties of chitosan. The antibacterial properties of chitosan-based wound dressings can be further enhanced by incorporating metallic nanoparticles into them, such as silver, zinc, titanium, etc. The incorporation of silver nanoparticles into chitosan-based wound dressings has been widely explored in the design of antimicrobial wound dressings. The incorporation of silver nanoparticles into chitosan-based wound dressings promotes accelerated wound-healing processes due to enhanced antimicrobial activity. The accelerated wound healing by these metal-based nanoparticles is via the regulation of re-epithelialization and inflammation without affecting the viability of normal cells. However, there have been few reports that evaluate these wound dressings in infectious animal models to prove their efficacy. The in vivo toxicity of silver nanoparticles still needs to be addressed, revealing the need for further preclinical and clinical trials. The fabrication of wound dressings incorporated with silver nanoparticles has not been fully explored, especially for wounds requiring immediate treatment. The possible interactions between silver nanoparticles and chitosan scaffolds that result in synergistic effects still need to be understood and studied. This review provides a comprehensive report on the preclinical outcomes of chitosan wound dressing materials loaded with silver nanoparticles for managing infected wounds.